Measurement Of Visitors' Perceptions And Attitudes Towards Business Location, Product Quality, And Promotion - Rusdan, Rusdan; Sulhaini, Sulhaini; Dayani, Rahman (Univeristas Islam Bandung, 2023)
This research seeks to confirm the internal views of café managers in Sembalun Area obtained from the results of previous research which stated that the main strength of cafes in Sembalun consists of three factors, namely business location, product quality, and promotion. The purpose of this research is to determine the perception and attitude of café visitors towards these three factors and provide alternative strategies that can be used in developing a café business. This study was a quantitative study using a descriptive approach The aspects analyzed were accessibility, distance, panoramic beauty, environmental cleanliness, environmental neatness, taste of dishes, cleanliness of dishes, variety of menus, neatness of presentation, content of promotion, types of promotional media, variations of promotional media, and frequency of promotion. The results of the analysis show that visitors' perceptions and attitudes towards business location, product quality, and promotion are at a Good/Positive level but with an average value that is close to the lower limit of the good level value. Business location is a key factor in the success of café business in Sembalun Area with the highest perception and attitude values. In addition, promotion is a very crucial factor because it has the lowest perception and attitude values. Therefore, the alternative strategy offered is to develop more massive and creative promotions using social media with a wide market coverage and increasing the capacity of service personnel and café managers. This research also provides more detailed solutions to implement the suggested strategy.